Bleeding in a 43 Year Old Female: A Rare Disease - Nwabundo Nwankwo; Olayinka Akinola; Aibek E. Mirrakhimov; Nkemakolam A. Iroegbu (Case Reports in Medicine)
A 43-year-old gravida 2 para 2 Caucasian female with a past medical history of menorrhagia secondary to uterine fibroids and thyroid disease presented to the emergency department with complaints of bruising in her oral mucosa and vaginal bleeding. One week prior to this presentation, she was transfused with two units of packed red blood cells because of symptomatic anemia secondary to menorrhagia. Physical examination was normal, except for petechiae on the abdomen and the lower extremities as well as purpuric lesions on the buccal mucosa. Blood work revealed thrombocytopenia. Posttransfusion thrombocytopenia was suspected. The patient was transfused with washed and leukoreduced platelets and treated with steroids and intravenous immunoglobulins. Laboratory studies demonstrated that she was homozygous for the HPA-Ib/1b platelet gene and positive antibodies against class 1 HLA and platelet glycoproteins. The patient responded well to treatment, with normalization of her platelet count.